Morphological and Molecular Assessment of Durian Germplasm in Malaysia - Santoso, Panca Jarot (2004)
Genetic resource management is essential for the continuity of improvement and production of durian. It involves maintaining associated data, and characterising and assaying highly heritable morphological and molecular traits for taxonomic study, genetic improvement, quality assurance and management purposes. The objective of this study was to determine the genetic variations of durian germplasm in Malaysia, based on morphological traits and PCR-RFLP on chloroplast DNA and ribosomal DNA regions.